2011
DOI: 10.1111/j.1365-2486.2011.02575.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen source and pCO2 synergistically affect carbon allocation, growth and morphology of the coccolithophore Emiliania huxleyi: potential implications of ocean acidification for the carbon cycle

Abstract: Coccolithophores are unicellular phytoplankton that produce calcium carbonate coccoliths as an exoskeleton. Emiliania huxleyi, the most abundant coccolithophore in the world's ocean, plays a major role in the global carbon cycle by regulating the exchange of CO 2 across the ocean-atmosphere interface through photosynthesis and calcium carbonate precipitation. As CO 2 concentration is rising in the atmosphere, the ocean is acidifying and ammonium (NH 4 + ) concentration of future ocean water is expected to rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 70 publications
2
64
0
Order By: Relevance
“…Unfortunately, these studies are difficult and time consuming to conduct, but they yield critical information to correctly predict additive or synergistic effects of elevated pCO 2 and other changing parameters that will characterize the future oceans. Elevating pCO 2 concentration and shifting nitrogen source have a synergistic effect on calcification [24], and here we indicate that the responses of E. huxleyi to elevated pCO 2 might be offset by simultaneously increasing temperature. Responses of E. huxleyi to simultaneous shifts in multiple environmental parameters add to the complexity of understanding how coccolithophores will respond to the future ocean and the subsequent feedback to the global carbon cycle.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Unfortunately, these studies are difficult and time consuming to conduct, but they yield critical information to correctly predict additive or synergistic effects of elevated pCO 2 and other changing parameters that will characterize the future oceans. Elevating pCO 2 concentration and shifting nitrogen source have a synergistic effect on calcification [24], and here we indicate that the responses of E. huxleyi to elevated pCO 2 might be offset by simultaneously increasing temperature. Responses of E. huxleyi to simultaneous shifts in multiple environmental parameters add to the complexity of understanding how coccolithophores will respond to the future ocean and the subsequent feedback to the global carbon cycle.…”
Section: Resultsmentioning
confidence: 91%
“…Allowing for multiple days to pass between sampling for physiological parameters ensured that the population of cells had been replaced completely between collection points, given the high growth rate in our chemostats of 1.1 d 21 (more than one division per day). This sampling strategy is routinely used for continuous culture experiments, as cells several generations apart represent independent samples of the same population [13,24,31,36].…”
Section: (B) Sampling and Analyses Of Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased [CO 2 ] might directly benefit biomass production either by enhancing the carboxylation reaction at RubisCO (Raven et al 2005), by reducing CO 2 leakage (Rost et al 2006), or by allowing a down-regulation of activity of the energyintensive carbon concentrating mechanism (CCM; Kranz et al 2010). It has also been indicated that responses to OA are often modulated by light intensities (Kranz et al 2010; Lefebvre et al 2010). Investigating the underlying processes as well as the modulating effects of energy availability will therefore improve the understanding of the origins of measured responses.…”
mentioning
confidence: 99%
“…An increased proton (H + ) concentration may impair transport processes, such as the uptake of inorganic carbon (C i ) or calcium ions (Ca 2+ ), being dependent on electrochemical membrane potentials (Mackinder et al 2010;Taylor et al 2011). Increased [CO 2 ] might directly benefit biomass production either by enhancing the carboxylation reaction at RubisCO (Raven et al 2005), by reducing CO 2 leakage (Rost et al 2006), or by allowing a down-regulation of activity of the energyintensive carbon concentrating mechanism (CCM; Kranz et al 2010).…”
mentioning
confidence: 99%